2004
DOI: 10.1063/1.1821636
|View full text |Cite
|
Sign up to set email alerts
|

Production and recovery of defects in phosphorus-implanted ZnO

Abstract: Articles you may be interested inReuse of AIP Publishing content is subject to the terms at: https://publishing.aip.org/authors/rights-and-permissions. Phosphorus ions were implanted in ZnO single crystals with energies of 50-380 keV having total doses of 4.2ϫ 10 13 -4.2ϫ 10 15 cm −2 . Positron annihilation measurements reveal the introduction of vacancy clusters after implantation. These vacancy clusters grow to a larger size after annealing at a temperature of 600°C. Upon further annealing up to a temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 46 publications
(54 reference statements)
7
77
0
Order By: Relevance
“…This is seen in both undoped and Al/Ga-doped thin films 21,[26][27][28] as well as in studies in bulk crystals. [10][11][12]22,25 Clusters of vacancies in ZnO have been observed mainly in implantation studies 4,23,[29][30][31][32][33][34][35][36][37][38] and also after heavy irradiation. 21 These vacancy clusters have been shown to disappear (become unstable) in thermal treatments at temperatures of about 800°C, with a single exception: the N-implantation damage is stable up to at least 1000°C in ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…This is seen in both undoped and Al/Ga-doped thin films 21,[26][27][28] as well as in studies in bulk crystals. [10][11][12]22,25 Clusters of vacancies in ZnO have been observed mainly in implantation studies 4,23,[29][30][31][32][33][34][35][36][37][38] and also after heavy irradiation. 21 These vacancy clusters have been shown to disappear (become unstable) in thermal treatments at temperatures of about 800°C, with a single exception: the N-implantation damage is stable up to at least 1000°C in ZnO.…”
Section: Discussionmentioning
confidence: 99%
“…4, i.e., a strong peak at 377 nm and a weak peak at 390 nm. The former peak is due to the recombination of free excitons from the conduction band edge (EC) and the valance band edge (EV), and the latter peak is supposed to be generated by the radiative transitions from Zn interstitial state (IZn) to valance band edge (EV) [31]. After annealing the peak at 390 nm disappeared, indicating that the post-annealing can decrease the defect density of Zn interstitials (IZn) of the films by adopting more oxygen atoms, thus improving the degree of crystallinity.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed electron and ion irradiation experiments with subsequent thermal annealings (Tuomisto, Saarinen, Look, and Farlow, 2005;Chen et al, 2007;Chen, Betsuyaku, and Kawasuso, 2008;Zubiaga et al, 2008;Knutsen et al, 2012) have shown that the radiation hardness originates from the high mobility of Zn sublattice damage already at room temperature in ZnO. The quest for p-type ZnO has led to many doping-by-implantation studies (Chen et al, , 2005a(Chen et al, , 2005bChen, Maekawa et al, 2005;Børseth et al, 2006Børseth et al, , 2008Neuvonen et al, 2009 where the Zn sublattice damage (Zn vacancies) has been shown to strongly interact with the implanted impurities. Section IV.H discusses the role of Li in positron studies of ZnO-this abundant impurity in bulk crystals grown by the hydrothermal method has led to some scatter in positron data published over the years (Johansen, Zubiaga, Makkonen et al, 2011).…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%